2017
DOI: 10.1016/j.gaitpost.2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Carrying asymmetric loads during stair negotiation

Abstract: Individuals often carry items in one hand instead of both hands during activities of daily living. The combined effects of carrying asymmetric loads and stair negotiation may create even higher demands on the low back and lower extremity. The purpose of this study was to investigate the effect of symmetric and asymmetric loading conditions on L5/S1 and lower extremity moments during stair negotiation. Twenty-two college students performed stair ascent and stair descent on a three-step staircase (step height 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
(36 reference statements)
2
7
0
Order By: Relevance
“…The above study assessed symmetrical load and asymmetrical load in the preferred hand and included only young and older females, limiting the generalisability of their findings to both genders across the entire adult age spectrum. When carrying or holding loads, individuals are likely to interchange between the preferred and non-preferred hand, to offset fatigue effects of prolonged load carriage and to allow the opposite hand to be free for other activities (Wang & Gillette, 2017). From this perspective, it is important to consider postural sway while holding loads with the preferred and non-preferred hand.…”
Section: Introductionmentioning
confidence: 99%
“…The above study assessed symmetrical load and asymmetrical load in the preferred hand and included only young and older females, limiting the generalisability of their findings to both genders across the entire adult age spectrum. When carrying or holding loads, individuals are likely to interchange between the preferred and non-preferred hand, to offset fatigue effects of prolonged load carriage and to allow the opposite hand to be free for other activities (Wang & Gillette, 2017). From this perspective, it is important to consider postural sway while holding loads with the preferred and non-preferred hand.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that 1) peak external knee varus, hip abduction, and L5/S1 contralateral bending moments would be increased during unilateral load carriage as compared to bilateral load carriage, and 2) peak external knee varus and hip abduction moments would be significantly higher during unloaded limb stance as compared to loaded limb stance during unilateral load carriage. [18] to determine a minimum estimated effect size of 0.96 with an alpha error probability of 0.0125 (adjusted by the number of variables) and a power of 0.90. Participants were free of any pathology that would affect them while walking on stairs or prevent them from being able to carry a 20% BW load.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, during the daily tasks, stair climbing is typically performed while carrying extra loads such as babies, grocery bags, resulting in further demands on the lower extremity and also raising the risk of falls and related injuries [14,15]. A study conducted by Hall and collages (2013) showed that when participants were loaded with a (13.6 kg) in the front or the back of their bodies, representing approximately 20% of their body weight, the external knee adduction moments increased compared to locomotion without loading.…”
mentioning
confidence: 99%
“…Whereas, stair ascent had a significant increase in knee adduction moments compared to stair descent task [16]. The impact of symmetric and asymmetric load conditions on the kinematics of stair gait has been investigated by Wang and Gillette (2017). The results of their study showed that when participants were asked to carry a 20% unilateral (asymmetrical) external loads during stair ascent, they demonstrated a significant increase in moment magnitudes of trunk bend, hip abduction, and external knee varus [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation